Analysis Of The Influence Of Company Size, Economic Performance, Leverage, And Foreign Ownership On Corporate Social Responsibility Disclosure - Rasyid, Dwiyan Al (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2022)
Purpose: This research aims to analyze the relationship between leverage, profitability, and foreign ownership on the disclosure of Corporate Social Responsibility in the mining sector listed on the Indonesia Stock Exchange (IDX). This study was conducted because, nowadays, companies globally are not only oriented toward high performance profits, but also towards social and environmental issues. Methodology: The population of this research was 114 mining companies listed on the IDX during 2013-2015, with purposive sampling techniques resulting in 87 mining companies. Multiple linear regression analysis was used to determine the effect of independent variables (company size, economic performance, leverage, and foreign ownership) on the dependent variable of Corporate Social Responsibility. The Corporate Social Responsibility index was measured using indicators disclosed by companies with the number of indicators set out in the G4 by the Global Reporting Initiative (GRI). Company size was determined by the amount of assets, Economic Performance was defined by return on assets (ROA), leverage was defined by the debt-to-asset ratio (DAR), and Foreign Ownership was defined by the amount of foreign ownership divided by the number of outstanding shares. Findings: The results of this research show that Company Size, Economic Performance, and Foreign Ownership influence the disclosure of Corporate Social Responsibility, in contrast, Leverage does not influence the disclosure of Corporate Social Responsibility. Novelty: This research uses a more comprehensive measurement standard for CSR disclosure than previous research, which used the G3 version 3.0 standard with 79 disclosure items. In this research, the G4 version 4.0 standard released by the Global Reporting Initiative (GRI) is used, which has 91 disclosure items Keywords: Corporate Social Responsibility, Company Size, Economic Performance, Leverage, and Foreign Ownership.